Hepatic Manifestations of 3-Hydroxy-3-Methylglutaryl-Coenzyme-A Lyase Deficiency in Saudi Patients: Experience of a Tertiary Care Center - Holdar, Sinan; Rahbeeni, Zuhair; Ramzan, Khushnooda; Imtiaz, Faiqa (Journal of Pediatric Genetics, 2020)
3-Hydroxy-3-methylglutaryl-coenzyme-A lyase (HMGCL) deficiency, a rare autosomal recessive disorder, is caused by a homozygous or compound heterozygous mutation in the HMGCL gene (chromosome 1p36.11). HMGCL catalyzes the final step of leucine degradation and plays a key role in ketone body formation. Several studies have reported general hepatic findings (e.g., hepatomegaly) in patients with HMGCL deficiency, but currently, there are no available data regarding the incidence and epidemiology of liver involvement. The main objective of our study was to investigate the overall clinical manifestations, laboratory findings, genotype, and presence of hepatic involvement in Saudi patients with HMGCL deficiency. A retrospective chart review of patients with HMGCL deficiency including those with a documented hepatic manifestation was performed at the King Faisal Specialist Hospital & Research Centre in Riyadh, Saudi Arabia. We evaluated 50 cases of HMGCL deficiency. Hepatic findings were found in 17 patients at the time of diagnosis. The mean age of hepatic presentation was 135 days, and the median age was 56 days (range: 2–315 days). Hepatomegaly was found in 65%, abnormal biochemical profile in 47%, and an abnormal imaging in 53% of patients. The most frequent mutation in this cohort was the p.Arg41Gln founder mutation (59%). In comparison to data from the current literature, HMGCL deficiency can be considered as a diagnostic metabolite for hepatic manifestations and requires appropriate evaluation, including molecular genetic analysis.
Keywords: HMGCL deficiency; hepatic manifestations; hepatomegaly; mutation; Saudi Arabia